Parental involvement in english homework tasks: bridging the gap between school and home (2009)
This paper explores the concept of parental involvement in English homework tasks as a way to include parents in the educational community. This descriptive study was carried out in a female public school with 10 students from third and fourth grades and their parents. In order to obtain the information, different instruments were used: artifacts, interviews, questionnaires and observations. After analyzing the data, it was stated that parental involvement was seen as a means to bridge the gap between the school and home. The findings also showed the possibility of learning from each other and the importance of homework tasks as interactional and learning spaces among parents and children. Key words: School and home connections, parental involvement in homework tasks Este artículo explora el concepto de la participación de los padres de familia en el desarrollo de las tareas de inglés, como una forma de incluir a los padres de familia en la comunidad educativa. Este estudio descriptivo se realizó en un colegio público femenino, con diez estudiantes de tercero y cuarto de primaria y sus padres. Para la recolección de la información se utilizaron diferentes instrumentos: artefactos, entrevistas, cuestionarios y observaciones de clase. Después de analizar la información se encontró que la intervención de los padres de familia se percibió como un medio para crear lazos entre la casa y el colegio. Los resultados también mostraron la posibilidad del aprendizaje mutuo y la importancia de las tareas como espacios de interacción y aprendizaje entre padres e hijos. Palabras clave: Conexiones entre la escuela y la familia, soporte de los padres de familia en las tareas escolares